Sliding Vector Fields via Slow-Fast Systems - Llibre, Jaume; da Silva, Paulo R. [UNESP]; Teixeira, Marco A. (Belgian Mathematical Soc Triomphe, 2008)
This paper concerns differential equation systems on R(n) with discontinuous right-hand sides. We deal with non-smooth vector fields in R(n) having a codimension-one submanifold M as its discontinuity set. After a regularization of a such system and a global blow-up we are able to bring out; some results that bridge the space between discontinuous systems and singularly perturbed smooth systems.
Keywords: Regularization; vector fields; singular perturbation; discontinuous vector fields; sliding vector fields